Monocytes engineered with iSNAP inhibit human B‐lymphoma progression - Haohsiang Wu; Siamak Amirfakhri; Hsin‐Hung Lin; Hannah Hollandsworth; Filemoni Filemoni; Yahan Liu; Yiqian Wu; Julie Y. S. Li; Hongquan Xu; Shu Chien; Michael Bouvet; Yingxiao Wang (Wiley, 2022)
Abstract Monocytes are important regulators for the maintenance of homeostasis in innate and adaptive immune system and have been reported to play important role in cancer progression. CD47‐SIRPα recognition is a coinhibitory immune signal to inhibit phagocytosis in monocytes and macrophages and has been well‐known as the "Don't eat me" signal. By using an approach of integrated sensing and activating proteins (iSNAPs), we have rewired the CD47‐SIRPα axis to create iSNAP‐M which activates pathways in engineered human monocytes (iSNAP‐MC). The mRNA expression levels of the monocyte/macrophage markers CD11b, CD14, and CD31 are upregulated in iSNAP‐monocytes (iSNAP‐MC). With PMA induction, the iSNAP‐MC‐derived macrophages (iSNAP‐MΦ) showed upregelation in CD86 and CD80, but not CD206. TNFα expression and secretion were also increased in iSNAP‐MΦ. Furthermore, the injection of iSNAP‐MC into mice bearing human B‐lymphoma tumors led to the suppression of tumor progression. Therefore, the engineered monocytes, via blockage of coinhibitory immune signals by rewiring CD47‐SIRPα axis, can be applied to suppress target tumors for cancer immunotherapy.